A Cross-Sectional Study of Perceived Stress, Mindfulness, Emotional Self-Regulation, and Self-Care Habits in Registered Nurses at a Tertiary Care Medical Center. (February 2019) - Vivian, Elaina; Oduor, Hellen; Arceneaux, Sharina R.; Flores, Jasmine A.; Vo, Allison; Madson Madden, Barbara
Introduction: Workplace stress and burnout may influence nurses' physical and emotional well-being, which can impact the quality of care patients receive and their overall satisfaction with their hospitalization. Objectives: The objectives of the study were to evaluate whether there are significant statistical relationships between nurses' perceived stress, frequency of stressors, mindfulness, emotional self-regulation, self-care habits, and patient satisfaction scores. Methods: The study took place over the course of 4 weeks. In this study, 340 nurse participants were surveyed using cross-sectional voluntary sampling design. The survey included previously developed and validated instruments. SAS v. 9.4 was used for statistical analysis. Results: Significant differences were noted in average patient satisfaction scores by perceived stress; major nursing units in the Death and Dying, Conflict with Physicians, Lack of Support, and Work Load subscales of the Nursing Stress Scale; and major nursing units and dispositional mindfulness. Conclusions: Hospital administrators can use this information in their organizations and set priorities and tailor mindfulness-based stress-reduction interventions for nursing professionals.